WANDERINGS: RESEARCH AND FORMATION AS A SUBJECTIFYING PROCESSUALITY - Juliano dos Santos; Kátia Maria Kasper (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This work seeks to explore the relationship between body, subjectivity, and formation of some aspects that involve the "making of research," whose implementation took place between 2013 and 2015. The cartography (DELEUZE; GUATTARI, 2011; PASSOS et all, 2009; ROLNIK, 1989) elected by us as a method strived to accompany encounters with bodies, dance, contact improvisation, bio-dance, and lives in formation: "Dance and body expression." This activity was integrated, in the second semester of 2013, the set of activities of the pedagogical axis "Interações Culturais e Humanísticas" at the Universidade Federal do Paraná, Setor Litoral. There were some contributions to the field of education through the intensities mobilized during the research's production. The process of formation of a researcher presenting smaller elements, minor elements, not teaching itself, the representation or the discovery of the world, but research, movement, doubt, and the invention of worlds, mediation of desire. In this sense, the text that we present proposes a) point out some encounters that resonated with the body of the researcher and b) explore the effects that, in intensity, mobilized and continue to mobilize a process of formation. Keywords: Formation. Experimentation. Body. Subjectivity.